Organizational Commitment of White Collar Employees in Damansara Heights, Kuala Lumpur - Ling, Lee Xin; Yuen, Joyce Leu Fong (Journal of Social Economics Research, 2014)
Committed workforce has now become a competitive advantage of all types of organizations. However, employees’ organizational commitment is comparatively lower now if compare to the past. The main aim of this research is to identify whether there is a significant relationship between personal characteristics and organizational commitment. By understanding personal characteristics that predict organizational commitment, organizations could take necessary actions to improve employee commitment levels before greater losses are incurred. In essence, results from this survey indicate that age group, educational level and organizational tenure have significant statistical differences in organizational commitment.